CONCEPT OF STATE POWER UNDER THE RULER OF MACHIAVELLI AND THE ACQUISITION OF POWER BY THE THAI COUP JUNTA - Wijitwatchararak, Kanjira; Panyaruno, Phramaha Arun; Phathong, Ketsada; Santirungroj, Supattra; Phrakrupaladsuwatthanaphromajariyakhun (Journal of Yanasangvorn Research Institute Mahamakut Buddhist University, 2023)
After the change of government from an absolute monarchy to a democratic system with the King as the head of state. The political situation of the Thai state has seen 13 coups. The junta has claimed the legitimacy of seizing power by reasoning that to resolve conflicts and chaos in the country, the study of the concept of state power through Machiavelli writing “The Prince". The study found that the parallel between the idea of state power under Machiavelli’s ruler and the acquisition of power by the Thai coup d’état. Since the three characteristics of parents are: 1. Parents do not need to keep their promises. considered from solving political problems by coup d’état which is not in accordance with the mechanism of democracy, 2. looks like both a lion and a fox that is to say, power is used to create fear, is the nature of the lion and the use of constitutional mechanisms to maintain power and 3. the Thai coup d’état did not apply principles based on virtue. Because a coup is a process of changing the government by infringing methods. and lead to the way of obtaining the power of the Thai coup d’état When considering the reasons for the seizure, it relates to the interests, acquisition and retention of military power. This is evident from the history of coups in all eras.